Juridification and politics: From the dilemma of juridification to the paradoxes of rights. (October 2014) - Loick, Daniel
The article starts with the observation of an ambivalence inherent to the politics of juridification. On the one hand, some spheres of the life-world such as the family and the school are often places of exploitation, degradation and humiliation and therefore seem to require the implementation of legal protection for their members. At the same time, the demand for rights seems somehow to grasp too little, would be inadequate or even counterproductive. How can this ambivalence be politically dealt with? I first briefly reconstruct Jürgen Habermas' concept of juridification. I believe that Habermas works with an image of the family and the school as communicatively constituted and juristically uncompromised milieux, which proves to be highly questionable. In a second step I consider Axel Honneth's theory of the absolutization of legal freedom as offered in his recent work Freedom's Right . Honneth sidesteps several problematic implications of the Habermasian thesis of colonization, but still tends to underestimate the dominant patriarchal power relations in the spheres of the family and the school. Finally, I pursue Honneth's own suggestion that a new notion of politics is required for understanding contemporary struggles for recognition, which overcomes the statist tendencies of liberalism. I therefore propose to shift the perspective on the phenomenon of juridification, viewing it instead from the standpoint of the agents themselves, by turning to Wendy Brown's feminist theory on the paradoxes of rights.